PATIENTS’ SATISFICATION AS THE QUALITY INDICATOR OF NURSING - Beta, Gunta; Role, Dita; Berloviene, Dina; Balkena, Zane (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Patients, during their stay at hospital, have the right to receive qualitative care and patients’ wellbeing depends on it. Patients’ wellbeing is based on satisfaction with care, which is influenced by, made by several conditions: communication of nurses, professionalism, education and timely provision thereof. Research aim: analyse the satisfaction of patients with the care provided by nurses. Research methods: Quantitative research method – original questionnaire “Newcastle Satisfaction with Nursing Scale” (NSNS).The results of the research: Patient who gives the assessment on nursing quality, with his sense of health condition of the specific period, general and individual requirements, personalized wishes and expectations can influence the satisfaction assessment, because he always is the source subjective variations. Even though the level of patients’ satisfaction is important and considerable indicator for nursing quality, by means of which it is possible to determine the efficiency of the provided care. This is a real means to identify the implemented fields of nursing aims, and improve the process if required, to ensure the quality. Nursing quality is based on patient-centred approach to achieve the common preferable health-care results.